Microbiological analysisof packed fruit juices locally available in Jaipur, India - NEHA GHEEK BATRA; AMEETA SHARMA; NEHA AGARWAL (International Journal of Pharma and Bio Sciences, 2016)
Present investigation attempted to resolve the microbiological and biochemical attributes of the fruit juices collected from outlets of Jaipur city, India. In the study two samples of different brands of packed fruit juice (Brand A and Brand B) were screened for total aerobic mesophilic bacterial counts, fungal count and the coliform counts. Samples were of acidic pH ranging from 4 to 6. Samples were found to harbor viable bacteria within the range between 101 -103 cfu/ml. However the total microbial counts were within acceptable standards for human consumption. These counts are suggestive of bacterial contamination of the packaged fruit juice during handling since they are liquid, which could have contributed to the development as well as multiplication of these contaminants. Drug resistance among the isolates was found against ampicillin and chloramphenicol.